Thermal decomposition of the hydrated basic carbonates of lanthanides and yttrium in CO2 atmosphere - D'Assunção, L.Moscardini; Ionashiro, Massao [UNESP]; Rasera, D. E.; Giolito, I. (My University, 1993)
The hydrated basis carbonates of lanthanides and yttrium were prepared by precipitation from homogeneous solution via the hydrolysis of urea, without the addition of an auxiliary anion. Thermogravimetry, derivative thermogravimetry (TG-DTG), and differential thermal analysis (DTA) have been used in the study of these compounds in CO2 atmosphere. The results lead to the composition and thermal stability of the studied compounds, and also to a comparative study with reported results in air atmosphere. © 1993.